THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN DEVELOPING STUDENTS' READING SKILLS - Isoqova Odina Boxodir qizi, (Ustozlar uchun, 2025)
In today's ESL classrooms, reading is regarded as a fundamental language skill crucial for both academic success and effective communication. Conventional reading resources, which are typically designed specifically for educational purposes, often struggle to engage students or accurately represent how language is used in everyday situations. As a result, there is a growing trend to use authentic materials—such as narrative stories, poems —sourced from the real world to connect classroom learning with practical language use.